Differences in performance indicators between successful and unsuccessful Teams in UEFA-EURO 2012 - Mitrotasios, M. (Biology of Exercise, 2018)
The aim of the present study was to investigate the differences between successful and unsuccessful teams in terms of game-related statistics and performance variables. A total of 31 matches from UEFA-EURO 2012 were analyzed and 2 matches were excluded from analysis because the matches ended in a goalless draw. Data were analyzed using descriptive statistics and non-parametric chi-square analysis. Results revealed that, successful teams scored more goals, had longer ball possession, higher total attempts and attempts on target, won more corners and suffered more fouls, while unsuccessful teams had more attempts off target, conceded more yellow and red cards and committed more fouls. Concerning performance variables, successful teams had a higher proportion of goals scored in the second half, through open play and counter attack, while unsuccessful teams scored more goals through set plays. Successful teams scored more goals in 2nd half, while first goal effect had a greater impact on the final result of the match. This should provide valuable information for coaches and players, in order to guide the training process, but also to adjust their tactical plan before and during football matches.